Penegakan Hukum terhadap Pelaku Tindak Pidana Human Trafficking Berdasarkan Putusan (Nomor:3107/Pid.Sus/2018/PN Mdn) - Ronaldo Faomasi Z; Dewi Ervina Suryani; Ari Oktario Ginting; Chaka Waldo Sitompul (Mahesa Research Center, 2022)
The writing is to know law enforcement of the criminal trafficking of human trafficking based on ruling number 3107/ pid. SUS /2018/ pn MDN. The research method used in this writing was normative-that is, legal research that is conceptualized as written in legislation. The source of the legal material used was secondary data. The data-gathering technique used library studies and then qualitative data are analyzed. The study has a conclusion that the high crime rate of human trafficking shows yet the government's efforts to implement the protection of human trafficking victims are serious. Law enforcement is deemed to be lacking sterility to have a lasting effect on perpetrators. The crime of trafficking people is organized crime and all the perpetrators have different roles. Law enforcement in the 2007 statute number 21 was strengthened by the release of the amendment number 69 in 2008. The law policy against human trafficking according to rule number 3107/ pid. SUS /2018/ pn MDN used the penal approach that has been applied to the penal penal system in the theory of law enforcement and the coping of crime of the application of criminal law.